2019
DOI: 10.3390/ijerph16245157
|View full text |Cite
|
Sign up to set email alerts
|

A PISA-2015 Comparative Meta-Analysis between Singapore and Finland: Relations of Students’ Interest in Science, Perceived ICT Competence, and Environmental Awareness and Optimism

Abstract: The aim of the present study is twofold: (1) to identify a factor structure between variables-interest in broad science topics, perceived information and communications technology (ICT) competence, environmental awareness and optimism; and (2) to explore the relations between these variables at the country level. The first part of the aim is addressed using exploratory factor analysis with data from the Program for International Student Assessment (PISA) for 15-year-old students from Singapore and Finland. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…The relationship between eco-centric-oriented dispositions and digital-environmental awareness is positive and significant in the presence of the digital expertise mediator. This finding aligns with previous studies, which found that ICT competencies can mediate environmental optimism [100]. However, it is important to note that this positive association is primarily evident at higher levels of digital expertise.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between eco-centric-oriented dispositions and digital-environmental awareness is positive and significant in the presence of the digital expertise mediator. This finding aligns with previous studies, which found that ICT competencies can mediate environmental optimism [100]. However, it is important to note that this positive association is primarily evident at higher levels of digital expertise.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, this result suggests that male students are less aware of applying cyber-hygiene best practices, making them the most likely cyber victims. Thus, the results indicate the need to boost additional cyber-hygiene awareness actions for male students [29,34,62]. As highlighted earlier, female students in KSA universities are segregated and do not have direct contact with their male lecturers [15,63].…”
Section: Discussionmentioning
confidence: 86%
“…Recent research indicates that DS are required to access the internet, as well as to analyze and utilize online content [ 20 , 21 , 22 , 23 ]. Moreover, research has revealed that some students have the digital skills to be digital natives while others are like digital immigrants [ 21 , 24 , 25 , 26 ]. Others indicate that most students learn and develop their digital skills outside of formal studies, which further supports the notion of digital skills being developed for other purposes than learning [ 20 , 27 , 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%